A Substrate‐Induced Fabrication of Active Free‐Standing Nanocarbon Film as Air Cathode in Rechargeable Zinc–Air Batteries. Issue 7 (7th December 2021) - Yan, Dafeng; Xia, Chenfeng; He, Chaohui; Liu, Qingqing; Chen, Guangda; Guo, Wei; Xia, Bao Yu
Abstract: Designing cost‐effective and high‐efficiency bifunctional electrocatalysts for both oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) occurred at air electrodes is vitally significant yet challenging for Zn–air batteries (ZABs). In this work, a zinc substrate induced fabrication is reported of free‐standing nanocarbon hybrid film which shows good bifunctional activity and can be directly used as the air electrode in the rechargeable ZABs. The designed nanocarbon film in Zn–air battery provides a satisfactory power density of 185 mW cm –2 and cycling stability for 1200 h under the current density of 10 mA cm –2 . This hybrid film also gives a solid‐state ZAB excellent flexibility with a power density of 160 mW cm –2 . The free‐standing hybrid with abundant cobalt–nitrogen–carbon species coupled with porous architecture would be the original factor for its satisfactory performance of rechargeable ZABs. This work would pave an ideal way to design integrated electrode with high electrocatalytic performance towards electrochemical energy technologies. Abstract : A free‐standing nanocarbon film by a zinc substrate induced fabrication shows its bifunctional oxygen electrocatalysis for rechargeable Zn–air batteries.